Complementary and alternative medicine for the treatment of major depressive disorder - Nahas, Richard (College of Family Physicians of Canada, 2011)
OBJECTIVE: To review the clinical evidence supporting complementary and alternative medicine interventions for treating major depressive disorder. QUALITY OF EVIDENCE: PubMed was searched from January 1966 to February 2010 using the term depressive disorder in combination with St John’s wort, S-adenosylmethionine (SAM-e), exercise, acupuncture, omega-3 fatty acids, and folate. Only relevant human trials were selected. MAIN MESSAGE: In a large meta-analysis, St John’s wort was found to be equivalent to antidepressant drugs with fewer side effects. Exercise reduced depressive scores in 3 meta-analyses. Omega-3 fatty acids reduced depressive scores in a meta-analysis of 16 trials, but publication bias was identified. Oral SAM-e monotherapy reduced depressive scores in 4 of 5 small randomized controlled trials. Folate deficiency is associated with more severe and refractory depression, and supplementation reduced depressive scores in 2 of 3 randomized controlled trials. Acupuncture demonstrated limited efficacy in 1 meta-analysis and 5 other trials. CONCLUSION: St John’s wort and regular exercise appear effective in the treatment of depression. Acupuncture appears ineffective for depression, but it might offer other health benefits. Other promising therapies include SAM-e, omega-3 fatty acid, and folic acid supplementation in selected patients; further study is warranted.